Farm antibiotic use and resistance: account from a Red River Delta province of Vietnam - Vu, TQG (2024)
Background: Despite comprehensive plans to address antimicrobial resistance in agriculture, Vietnam saw limited progress on the ground. This could be the result of three problems, i.e. inadequate consideration of farmers’ concerns, lack of quantitative data while those available could not be easily understood, and very mixed evidence for how to reduce farm antibiotic use and resistance. Aim and research questions: The present DPhil aimed to provide an account of farm antibiotic use and resistance that would be relevant, understandable and actionable for Vietnamese farmers.